Innovative screening for OSAS in patients with head and neck cancer using the apneal application: Protocol for a prospective single-centre study - Lisa Baluta; Maxime Humbert; Emmanuel Babin; Rémy Morello; Emmanuel Micault (PLoS ONE, 2026)
Introduction OSAS is a common yet underdiagnosed condition, particularly among patients with head and neck cancers (HNC). Anatomical changes caused by the tumor or its treatments—surgery, radiotherapy, or chemotherapy—can promote the onset of OSAS. However, fatigue in these patients is often attributed solely to the cancer treatment itself, which may delay appropriate diagnosis and management. Methods This prospective single-center study aims to assess the clinical feasibility of OSAS screening in patients with HNC using an innovative mobile application, Apneal , which uses smartphone sensors to detect nocturnal respiratory events through an artificial intelligence algorithm. Fifty adult patients diagnosed with HNC will be included. Each patient will perform two home-based overnight recordings using the Apneal application: one at the time of diagnosis and another six months after local treatment. Clinical and quality-of-life questionnaires will be completed. The estimated AHI will be compared with symptomatology and, if necessary, confirmed by a standard respiratory polygraphy. Expected Results The primary outcome is the proportion of patients for whom Apneal data are usable at the 6-month follow-up after treatment. Secondary objectives include assessing the incidence of OSAS according to the oncologic treatments received, identifying high-risk profiles, and evaluating the impact of OSAS on quality of life. Discussion This study could pave the way for a systematic, simple, low-cost, and non-invasive OSAS screening in patients with HNC. Ultimately, the goal is to enable a more personalized and comprehensive approach to care in this vulnerable population.